Pressure vessel design simulation: Implementing of multi-swarm particle swarm optimization - Salih, Sinan Q.; Alsewari, Abdulrahman A.; Yaseen, Zeher M. (Association for Computing Machinery, 2019)
The new era knowledge of optimization algorithm is massively boosted recently. Among several optimization models, multi-swarm approach has been proposed most recently for balancing the exploration and exploitation capability through the Particle Swarm Optimization (PSO) algorithm. The proposed multi-swarm model which is called Meeting Room Approach (MRA), is tested and evaluated based on solving normal and large-scale problems. In the current research, the feasibility of the proposed Multi-Swarm Particle Swarm Optimization (MPSO) is adopted to simulate mechanical engineering problem namely pressure vessel design (PVD). The results indicated the potential of the proposed MPSO model on simulating the PVD problem with optimum solution over the standalone PSO. Further, the current study results authenticated against other famous meta-heuristics. Overall, MPSO reported an excellent optimization solution with fast convergence learning process.